Attack of the shadow smashers - Cummings, Troy (Cummings, Troy. Notebook of doom, 2013)
The latest monsters threatening Stermont Elementary are shadowy shapeshifters that attach themselves to people, eat their shadows, and block out all light--but before he can think of a way to deal with them, Alexander has to deal with a startling revelation from his friend Nikki.